9(6a+7)-6-3a=

Simple and best practice solution for 9(6a+7)-6-3a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(6a+7)-6-3a= equation:


Simplifying
9(6a + 7) + -6 + -3a = 0

Reorder the terms:
9(7 + 6a) + -6 + -3a = 0
(7 * 9 + 6a * 9) + -6 + -3a = 0
(63 + 54a) + -6 + -3a = 0

Reorder the terms:
63 + -6 + 54a + -3a = 0

Combine like terms: 63 + -6 = 57
57 + 54a + -3a = 0

Combine like terms: 54a + -3a = 51a
57 + 51a = 0

Solving
57 + 51a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-57' to each side of the equation.
57 + -57 + 51a = 0 + -57

Combine like terms: 57 + -57 = 0
0 + 51a = 0 + -57
51a = 0 + -57

Combine like terms: 0 + -57 = -57
51a = -57

Divide each side by '51'.
a = -1.117647059

Simplifying
a = -1.117647059

See similar equations:

| 45/100=x/39 | | 3/5*12.6 | | 3g-3=5(3-g) | | 1/6*+2=-12 | | 1/3=(1/12)x | | (1/3)* | | -25=-5/6x | | w+y=8 | | 2ax+3x=5x | | 8senx=3cosx | | 54-9/2 | | X-4/5=5/6 | | (21-2a)+(126-5a)=180 | | 4x-24=60+2x | | 30+2x=-6(7x-5) | | 2x^2-98y^4= | | N+5=14+4n | | -4(j+k+g)= | | 4x-2(6x+4)=32 | | 8x^3-22x^2+5x=0 | | w^2-13-12w= | | 210/100=x/147 | | 7/9x^2-6=2 | | 3(12+7)=26 | | 3+2t=39 | | 12y^3+5y-2= | | 10x+3y=-9 | | (5/4)x^2-4=24 | | t=-13+(-3) | | y=2.4x-0.001x^2 | | 2b=90 | | 8sin^2x=5-10cosx |

Equations solver categories